ANALYSIS OF THE TECHNOLOGY OF MAKING OF CHAIR IN THE PROCESS OF PRODUCTION OF COMPANIES IN MACEDONIA - Doneva, Tatjana; Namicev, Mihail (Journal of process management and new technologies, 2019)
By analyzing the technology of making chairs it is necessary to define the elements that affect the quality of production. The analysis of the materials, the structural elements, the perfecting of the production process, the improvement of the ergonomic characteristics, as part of the technological process, influence the quality of the making of the chairs. Through certain analyzes of the production process in domestic companies, can improve quality and increase production. Analyzes of specific data from companies contribute to improving the economic and architectural aspects of the production of chairs. According to the research, we can conclude a certain influence of the characteristics of the chairs present in the whole technological process, in the selection of materials, in the way of production, as well as in the presence of products in world trends and markets.